Exploring Relationships Between Size and Function of Trunk Muscles, Injuries and Concussion in a Professional Rugby League Team - Julie A. Hides; Felix Leung; Melinda M. Franettovich Smith; Luke Anning; Peter Blanch; M. Dilani Mendis (Journal of Science in Sport and Exercise, 2025)
Purpose Examine for injury risk factors and establish clinical cut-off values related to size and function of trunk muscles. Methods A prospective study of 28 professional Rugby League players was conducted. Cross-sectional areas (CSAs) of the multifidus (MF), quadratus lumborum (QL) and ability to contract the abdominal and MF muscles were measured from pre-season ultrasound images. Playing season injuries resulting in games missed were recorded by club personnel. Logistic regression models were used to determine the adjusted odds ratios for trunk muscle measures as risk factors for playing season injuries. Results The adjusted odds ratio (OR) values indicated that if a player had a small MF muscle (< 9.98 cm 2 at L5; P = 0.032) or a small QL (< 10.8 cm 2 ; P = 0.045), their odds of more games missed due to season injuries was increased (OR MF = 9.4; 95% CI = 1.21–72.9; OR QL = 7.3; 95% CI = 1.1–51.6). For players with increased contraction of the MF (contraction > 7.2%; P = 0.028) and abdominal muscles (> 49.9%; P = 0.08), the odds of sustaining a concussion were increased (OR MF 14.5; 95% CI 1.3–159; OR transversus abdominis 6.2; 95% CI = 0.8–48.6). Conclusion As size and ability to contract trunk muscles are modifiable factors, further intervention studies targeting motor control of these muscles may be warranted.